Factors Associated With Caring Among Nursing Students in Rural Area, Indonesia: A Cross-Sectional Study - Prestasianita Putri; Ika Adelia Susanti; Said Mardijanto; Madiha Mukhtar (Department of Public Health, Faculty of Sport Science, Universitas Negeri Semarang, 2023)
Caring becomes an essential concept in fundamental nursing and is impactful in the quality of health services and nursing practice. However, factors in educational level among nursing students contribute to shaping and creating good caring behavior among nurses in clinical settings. The purpose of this study aimed to explore factors associated with caring among nursing students. A survey using a cross-sectional study was conducted in this study. It involved nursing students in a clinical phase amount of 256 respondents. The sampling technique was quota sampling and questionnaires were used to assess caring and organizational factors. The Chi-square test and binary logistic regression were employed to explore the determinant factors of caring behavior. Most of the percentage of nursing students caring behavior was 50% good category which was mostly aged 17-25 years (49.4%) and female (51.2%). Emotional (OR=3.49; 95% CI=1.45-8.44) and quantitative workload (OR=0.29; 95% CI=0.10-0.84) were significantly related to caring behavior among nursing students. The proportion of nursing students who have good and poor caring behavior was found equal. Moreover, significant results were also noted between emotional workload and caring behavior. Providing quality education is necessary to ensure nursing students can improve their ability to care for patients.